(untitled) (International Journal of Social Research & Innovation, 2018)
The research presented in this paper focused on studying the factors that influence writing in English among a group of secondary school students in Male’, Maldives. Face-to-face interviews and a self-administered questionnaire were employed for data collection. The findings revealed that motivational factors such as self-efficacy, interest, and attitude of students affected students’ performance in writing. Also, subject knowledge, composition skills, and the context of writing such as time allocation, classroom setting, and examination oriented teaching were primary factors which hindered students’ writing. These factors which hinder students to write are blended with research on self-efficacy to discuss strategies to develop competence and confidence in writing among adolescents struggling with writing in a second language.